Enhancement of the Transdermal Delivery of Nonsteroidal Anti-inflammatory Drugs Using Liposomes Containing Cationic Surfactants - Kuznetsova, Darya A.; Vasilieva, Elmira A.; Kuznetsov, Denis M.; Lenina, Oksana A.; Filippov, Sergey K.; Petrov, Konstantin A.; Zakharova, Lucia Ya; Sinyashin, Oleg G. (ACS omega, 2022)
New hybrid liposomes based on cationic amphiphiles with different structures of the head group (cetyltrimethylammonium bromide (CTAB), 3-hexadecyl-1-hydroxyethylimidazolium bromide (IA-16(OH)), 1-(butylcarbamoyl)oxyethyl-3-hexadecylimidazolium bromide (IAC 16(Bu)), and hexadecylmethylpyrrolidinium bromide (PR-16)) were developed for transdermal administration of nonsteroidal anti-inflammatory drugs. The different surfactant/lipid compositions were studied to obtain stable liposomes with high functionality. The hydrodynamic diameter of cationic liposomes was ∼110 nm. An admixture of cationic surfactants and PC liposomes improves the physicochemical properties of vesicles and transdermal diffusion rate and prolongs the release of drugs. Liposomal diclofenac sodium (DS) and ketoprofen (KP) were tested (using Franz cells) for transdermal penetration. Drug diffusion monitoring for 48 h demonstrated that the maximum DS and KP penetration through the synthetic membranes (Strat-M) is characterized by values of 255 ± 2 and 186 ± 3 μg/cm2, respectively. The influence of the surfactant head group on the properties (stability, release profile, permeability) of cationic liposomes was shown for the first time. While the drug specificity is evident for the rate of release, the permeability increases as follows: conventional liposomes < CTAB/PC < PR-16/PC < IAC-16(Bu)/PC < IA-16(OH)/PC for both medicines. The rat paw edema model was used to assess the anti-inflammatory effect of the IA-16(OH)/PC leader formulation in vivo. It was found that liposomal DS and KP are effective for relieving rat paw edema. It should be noted that DS-loaded hybrid liposomes demonstrated the highest therapeutic efficacy compared to conventional vesicles.